An integrated procurement assessment model for the measurement of development effectiveness and value for money in international development - Cook, Bryan Clifford (Curtin University, 2022)
This research examines the relationship between project success and procurement performance to identify predictors that contribute to Development Effectiveness (DE) and Value for Money (VFM) in international development. The findings indicate that the existing project evaluation criteria, used by the selected international development organisations, have inconsistencies and do not provide a reliable measurement of DE and VFM. The research contributes to theory on the measurement of DE and VFM in international development projects.